ANALISIS PENGARUH IMPLEMENTASI ENTERPRISE RISK MANAGEMENT TERHADAP KINERJA DAN NILAI PERUSAHAAN - Dinoyu, Muhammad Faiq; Septiani, Aditya (Diponegoro Journal of Accounting, 2020)
This study aims to examine the extent of implementation of enterprise risk management (ERM) has an effect on firm performance and firm value. To measure the level of ERM implementation, the study used six components that were sourced from governance and firm operating activities. This study also used board of commissioners, the percentage of independent commissioners, firm size, leverage, return on equity (ROE), and industry classification as control variables.            The population in this study consists of all public companies in the manufacturing sector listed on the Indonesia Stock Exchange from 2016 to 2018. Sampling of companies was using the purposive sampling method with a total of 103 companies used as samples in this study.            This study uses multiple linear regression analysis and robust regression for hypothesis testing. The results of this study indicate that the implementation of enterprise risk management (ERM) has a positive effect on improving firm performance and firm value as measured using return on assets (ROA) and Tobin's Q.